The Economic Nationalism within the European Union and the Single Market - case study of France, Germany and the United Kingdom - Gheorghiev, Olga (2015)
This paper examines the phenomenon of economic nationalism within market interactions of different economic models of governance in the European Union. The first section offers a retrospective of economic nationalism interpretations at different periods of time, with a focus on the past century. It also introduces the reader to new forms of economic nationalism, particular for the European integration context and which ultimately represent the subject of this paper. Next the study focuses on the particularities of the European economic model and its relation to state interventionism. It also attempts to identify EU's mandate of action and instruments in this direction, with a special attention to the key economic sectors and dominant forms of interventionism. The last chapter provides a closer look at national regulatory traditions of three economic models: British, German and French and traces approaches to economic nationalism within these distinct models of economic governance.